Real-World Evidence on the Prevalence of Molar Incisor Hypomineralization in School Children from Bucharest, Romania - Beatrice Ciocan; Mihai Săndulescu; Rodica Luca (MDPI AG, 2023)
Molar incisor hypomineralization (MIH) is an understudied and underrecognized clinical entity occurring in children. We performed a cross-sectional study to determine the real-world prevalence of MIH among school children undergoing routine dental checkups at one primary and middle school in Bucharest, Romania. Our study cohort consisted of 266 children with evaluable data, of which 143 (53.8%) were males, with a median age of 10 years old (interquartile range: 8-11 years). In this study cohort, we have identified a prevalence of 14.3% (n = 38 cases) of MIH. Among patients diagnosed with MIH, hypomineralizations were present in 47.4% of children on the maxillary first molar, 92.1% on the mandibular first molar, 94.7% on the maxillary incisor, 36.8% on the mandibular incisor, and 5.3% on the deciduous second molar. We identified the maxillary incisor and the mandibular first molar as the most important examined sites significantly associated with the presence of MIH (p < 0.0001 each), highlighting the importance of paying focused attention to these sites during routine dental care in children. In order to establish the diagnosis of MIH, findings of hypomineralization should be present on at least one permanent first molar, according to the case definition currently in use; this definition does not include findings on the incisors. Thus, our finding that hypomineralization of the maxillary incisors is significantly associated with MIH is particularly important. While incisor hypomineralization is not diagnostic of MIH, based on our results, we conclude that it should raise the suspicion of MIH and lead to an attentive examination of the permanent molars in order to establish timely diagnosis.